The family atmosphere and the coping to stress in adolescents of a general hospital and its associations to the clinic of end stage renal disease - Chalco-Flores, María Elizabeth (2019)
OBJECTIVE. To measure the association of Family Atmosphere (FA) and Stress Coping Strategies (SCS) in a sample of adolescents with end-stage renal disease (ESRD) of a general hospital. MATERIAL AND METHODS. During the year 2012, 36 teenagers of both genders with ESRD, under treatment with peritoneal dialysis (PD), hemodialysis (HD) and kidney transplant (KT), were evaluated with the Family Environment Scale (FES) and the Adolescent Coping Scale (ACSA), and also it was registered some sociodemographic and clinical variables. RESULTS. When comparing the results obtained by adolescents with ESRD with the normal values of the applied tests, we found that Conflict factor from the ECSF was the one with the greatest presence and the Search for Social Support of the SCS was the least employed. Particularly, adolescents in treatment with PD employed more the Lack of Coping of the EAE. CONCLUSIONS. In the treatment of the ESRD, it should be propitiated a more functional family atmosphere because the family is a support of the maintenance of the therapy Also, we must adopt measures to clarify and confront the adaptations of their SCS employed. The effectiveness of these interventions would provide a better prognosis of the ESRD.